Erythropoietin and the Nervous System - Höke, Ahmet (Springer US : Imprint: Springer, 2006)
Erythropoietin and the Nervous System is the first book of its kind to bring together researchers from many different disciplines of neuroscience to present a current state-of-the-art review of multiple aspects of erythropoietin research as it relates to the nervous system. Erythropoietin (EPO) is a chemokine hormone that is widely distributed throughout the body. In addition to its traditional role as a hormone that stimulates red blood cell production, in recent years many laboratories have shown that EPO can act as a neuroprotective compound in a variety of injury paradigms in the nervous system. Past experience with the relatively safety profile of this FDA-approved drug makes it an ideal candidate to take into clinical trials for neuroprotection. We are on the verge of major clinical trials using this drug for neuroprotection in diseases ranging from stroke, to transverse myelitis to chemotherapy-induced peripheral neuropathy. This book should stimulate new research on erythropoietin and the nervous system and bring new investigators to the field. It will benefit scientists and clinicians interested in neuroprotection in the broadest sense.